Leaves and Fruits Preparations of Pistacia lentiscus L.: A Review on the Ethnopharmacological Uses and Implications in Inflammation and Infection - Egle Milia; Simonetta Maria Bullitta; Giorgio Mastandrea; Barbora Szotáková; Aurélie Schoubben; Lenka Langhansová; Marina Quartu; Antonella Bortone; Sigrun Eick (MDPI AG, 2021)
There is an increasing interest in revisiting plants for drug discovery, proving scientifically their role as remedies. The aim of this review was to give an overview of the ethnopharmacological uses of Pistacia lentiscus L. (PlL) leaves and fruits, expanding the search for the scientific discovery of their chemistry, anti-inflammatory, antioxidative and antimicrobial activities. PlL is a wild-growing shrub rich in terpenoids and polyphenols, the oil and extracts of which have been widely used against inflammation and infections, and as wound healing agents. The more recurrent components in PlL essential oil (EO) are represented by α-pinene, terpinene, caryophyllene, limonene and myrcene, with high variability in concentration depending on the Mediterranean country. The anti-inflammatory activity of the oil mainly occurs due to the inhibition of pro-inflammatory cytokines and the arachidonic acid cascade. Interestingly, the capacity against COX-2 and LOX indicates PlL EO as a dual inhibitory compound. The high content of polyphenols enriching the extracts provide explanations for the known biological properties of the plant. The protective effect against reactive oxygen species is of wide interest. In particular, their anthocyanins content greatly clarifies their antioxidative capacity. Further, the antimicrobial activity of PlL oil and extracts includes the inhibition of Staphylococcus aureus, Escherichia coli, periodontal bacteria and Candida spp. In conclusion, the relevant scientific properties indicate PlL as a nutraceutical and also as a therapeutic agent against a wide range of diseases based on inflammation and infections.